The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/cb.2089
|View full text |Cite
|
Sign up to set email alerts
|

Transport and mobility decisions of consumers with disabilities

Abstract: People with disabilities are the world's largest minority stakeholder group, and they continue to face significant challenges in every aspect of their lives. This study explored the transport and mobility decisions of consumers with disabilities (CWDs) in the context of Nigeria, one of the world's largest developing countries, using the conservation of resources theory and the intersection of travel decisions, disability and country context regarding consumer behaviour. A total of 32 individuals with varying d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 66 publications
(143 reference statements)
1
22
0
Order By: Relevance
“…The physical limitations of PWMI in combination with the environmental barriers posed by the lack of, or poor condition of the UDFs make the roads unusable thereby creating further isolation and exclusion of this population group. These findings are in line with that of Mogaji, Bosah, and Nguyen (2022) who observed that conditions creating significant mobility exclusions and hardships to people with disability in Nigeria have to do with the quality (and the lack thereof) of pedestrian infrastructure and facilities. The physical barriers identified include nonexistence or poor design and maintenance of pedestrian and crossing facilities; high kerbs and narrow pavements; lack of bus stop facilities like shelter, waiting seats, and toilets; sloppy or slippery surfaces; poor coverage and condition of streetlights; vehicles with low usability; and discrimination on PWMI by drivers and other road users.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The physical limitations of PWMI in combination with the environmental barriers posed by the lack of, or poor condition of the UDFs make the roads unusable thereby creating further isolation and exclusion of this population group. These findings are in line with that of Mogaji, Bosah, and Nguyen (2022) who observed that conditions creating significant mobility exclusions and hardships to people with disability in Nigeria have to do with the quality (and the lack thereof) of pedestrian infrastructure and facilities. The physical barriers identified include nonexistence or poor design and maintenance of pedestrian and crossing facilities; high kerbs and narrow pavements; lack of bus stop facilities like shelter, waiting seats, and toilets; sloppy or slippery surfaces; poor coverage and condition of streetlights; vehicles with low usability; and discrimination on PWMI by drivers and other road users.…”
Section: Discussionsupporting
confidence: 91%
“…The act provided that every transport facility (including roads) shall be retrofitted to ensure the removal of barriers for PWD within five years of its commencement. But four years along the line, no single road (whether old or new) has effectively complied with the law as observed by Mogaji, Bosah, and Nguyen (2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These previous studies on marketplace accessibility have recognised the obstacles and difficulties for individuals experiencing vulnerability at the point of service interaction. Because PWDs are less likely to drive or own a car than the non-disabled, they often rely on public transportation infrastructures (Kwon and Akar, 2022; Mogaji et al , 2022a, 2022b). This concern is further reiterated by the informants from Yu et al ’s (2015) study on retail design for visually impaired customers, where all participants reported that mobility was the biggest challenge they faced.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, previous research on mobility behaviour has paid limited attention to (in)equality and its different forms in the mobility sector. The paper 'Transport and mobility decisions of consumers with disabilities' by Mogaji et al (2023) explores the transport and mobility decisions of consumers with disabilities in the context of Nigeria, using the conservation of resources theory and the intersection of travel decisions, disability and country context regarding consumer behaviour.…”
Section: Dear Editormentioning
confidence: 99%